Prediction of burr formation in fabricating MEMS components by micro end milling - Ali, Mohammad Yeakub; Omar, Mohd Aliff; Othman, Khairul Irman; Hung, Wayne N.P. (Trans Tech Publications Ltd., Switzerland, 2009)
This paper discusses burr formation in micromilling of AISI 304 stainless steel. Chip load, cutting speed and the application of coolant were chosen as the milling parameters. Experiments were conducted using 500 µm diameter tungsten carbide end milling tool. Milling parameters and measured burr height values were analyzed and statistical models were developed for the estimation of burr height. The models showed that the chip load and cutting speed both have direct and interactive contribution to burr formation. When micromachining without coolant, the burr height increases about 40% compared to that of machining with coolant. The optimized values of chip load and cutting speed were found to be 1 µm/tooth and 78 mms-1 respectively. The predicted burr heights were 5-7% larger than that of measured values.